Analisis Kedisiplinan Kerja Karyawan dengan Penggunaan Sistem Absensi Analog pada PT Sumber Mas Indah Plywood - Jihan Rohadatul Aisy; Heru Baskoro (MES Bogor, 2025)
Analog attendance systems are still widely used in various companies as a tool to record employee attendance. This study aims to analyze the level of work discipline among employees using analog attendance systems. The research data was collected through interviews with several employees, direct observation, and analysis of employee attendance reports at PT. Sumber Mas Indah Plywood over a specific period. The results of the study show that analog attendance systems have several major weaknesses, such as being prone to data manipulation like proxy attendance, inaccuracies in manual recording, and the loss or damage of attendance cards. Moreover, this system is considered inefficient as the manual recording process takes more time and does not support real-time monitoring of discipline. These weaknesses negatively impact employee discipline levels and the overall productivity of the company. The conclusion of this study is that the use of analog attendance systems is not effective in improving employee work discipline or in optimally managing attendance data. Therefore, the company is advised to consider upgrading to modern technology-based attendance systems, such as face recognition, to enhance accuracy, efficiency, and overall management of employee discipline.